Multithreaded Parallelization of Mechatronic Controllers on a Zynq Platform FPGA - Surmund, Sebastian

Applications of Evolutionary Computation - 17th European Conference, EvoApplications - I. Esparcia-Alcázar, Anna; Eiben, A.E.; Agapitos, Alexandros; Simões, Anabela; G.B. Tettamanzi, Andrea; Della Cioppa, Antonio; M. Mora, Antonio; Cotta, Carlos; Tarantino, Ernesto; Haasdijk, Evert; Divina, Federico; Fernández de Vega, Francisco; et al.

Analytic reliability evaluation for fault-tolerant circuit structures on FPGAs - Anwer, Jahanzeb; Platzner, Marco (IEEE International Symposium on Defect and Fault Tolerance in VLSI and Nanotechnology Systems (DFT))

Fast process variation analysis in nano-scaled technologies using column-wise sparse parameter selection - Ghasemzadeh Mohammadi, Hassan; Gaillardon, Pierre-Emmanuel; Yazdani, Majid; De Micheli, Giovanni (2014 IEEE/ACM International Symposium on Nanoscale Architectures (NANOARCH))

Adaptive load allocation for combining Anomaly Detectors using controlled skips - Berger, Mario; Erlacher, Felix; Sommer, Christoph; Dressler, Falko (2014 International Conference on Computing, Networking and Communications (ICNC))

Towards an Open Source IEEE 802.11p stack: A full SDR-based transceiver in GNU Radio - Bloessl, Bastian; Segata, Michele; Sommer, Christoph; Dressler, Falko (2013 IEEE Vehicular Networking Conference)

Timings matter - Bloessl, Bastian; Puschmann, Andre; Sommer, Christoph; Dressler, Falko (Proceedings of the 9th ACM international workshop on Wireless network testbeds, experimental evaluation and characterization - WiNTECH '14)

Towards a vehicular cloud - using parked vehicles as a temporary network and storage infrastructure - Dressler, Falko; Handle, Philipp; Sommer, Christoph (Proceedings of the 2014 ACM international workshop on Wireless and mobile technologies for smart cities - WiMobCity '14)

Towards a simulation framework for paraglider networks - Eckert, Juergen; Sommer, Christoph; Eckhoff, David (Proceedings of the 11th ACM symposium on Performance evaluation of wireless ad hoc, sensor, & ubiquitous networks - PE-WASUN '14)

SmartRevoc: An efficient and privacy preserving revocation system using parked vehicles - Eckhoff, David; Dressler, Falko; Sommer, Christoph (38th Annual IEEE Conference on Local Computer Networks)

Driving for Big Data? Privacy Concerns in Vehicular Networking - Eckhoff, David; Sommer, Christoph (IEEE Security & Privacy)

On the impact of street width on 5.9 GHz radio signal propagation in vehicular networks - Erlacher, Felix; Klingler, Florian; Sommer, Christoph; Dressler, Falko (2014 11th Annual Conference on Wireless On-demand Network Systems and Services (WONS))

The Role of Parked Cars in Content Downloading for Vehicular Networks - Malandrino, Francesco; Casetti, Claudio; Chiasserini, Carla-Fabiana; Sommer, Christoph; Dressler, Falko (IEEE Transactions on Vehicular Technology)

Short paper: Vehicle shadowing distribution depends on vehicle type: Results of an experimental study - Segata, Michele; Bloessl, Bastian; Joerer, Stefan; Sommer, Christoph; Lo Cigno, Renato; Dressler, Falko (2013 IEEE Vehicular Networking Conference)

Towards energy efficient smart phone applications: Energy models for offloading tasks into the cloud - Segata, Michele; Bloessl, Bastian; Sommer, Christoph; Dressler, Falko (2014 IEEE International Conference on Communications (ICC))

A networking perspective on self-organizing intersection management - Sommer, Christoph; Hagenauer, Florian; Dressler, Falko (2014 IEEE World Forum on Internet of Things (WF-IoT))

A cluster based architecture for intersection collision avoidance using heterogeneous networks - Tung, Lung-Chih; Mena, Jorge; Gerla, Mario; Sommer, Christoph (2013 12th Annual Mediterranean Ad Hoc Networking Workshop (MED-HOC-NET))

What influences dwell time during source code reading?: analysis of element type and frequency as factors - Busjahn, Teresa; Bednarik, Roman; Schulte, Carsten (ETRA)

Eye tracking in computing education - Busjahn, Teresa; Schulte, Carsten; Sharif, Bonita; Begel, Andrew; Hansen, Michael; Bednarik, Roman; Orlov, Paul; Ihantola, Petri; Shchekotova, Galina; Antropova, Maria (ICER)

Developing Coding Schemes for Program Comprehension using Eye Movements - Busjahn, Teresa; Schulte, Carsten; Kropp, Edna (PPIG)

Proceedings of the 9th Workshop in Primary and Secondary Computing Education, WiPSCE 2014, Berlin, Germany, November 5-7, 2014

RESOLVE: An Emotion Word Suggestion System Facilitates Language Learners’ Emotional Expressions - Chen, Mei-Hua; Chen, Wei-Fan; Ku, Lun-Wei (Proceedings of the AsiaCALL 2014)

Difference Computation for Grammar-Compressed XML Data - Böttcher, Stefan; Hartel, Rita; Thiele, Sebastian (Proceedings of the Second Australasian Web Conference)

Keyword Search on DAG-Compressed XML Data - Böttcher, Stefan; Brandenburg, Marc; Hartel, Rita (Proceedings of the Second Australasian Web Conference)

Efficient XML Keyword Search Based on DAG-Compression - Böttcher, Stefan; Hartel, Rita; Rabe, Jonathan (Database and Expert Systems Applications - 25th International Conference, DEXA 2014)

Preference-based learning of ideal solutions in TOPSIS-like decision models - Agarwal, M.; Fallah Tehrani, A.; Hüllermeier, Eyke (Journal of Multi-Criteria Decision Analysis)

Extended graph-based models for enhanced similarity search in Cabase - Krotzky, T.; Fober, T.; Hüllermeier, Eyke; Klebe, G. (IEEE/ACM Transactions of Computational Biology and Bioinformatics)

Learning from imprecise and fuzzy observations: Data disambiguation through generalized loss minimization - Hüllermeier, Eyke (International Journal of Approximate Reasoning)

Visualization of evolving fuzzy-rule-based systems - Henzgen, Sascha; Strickert, M.; Hüllermeier, Eyke (Evolving Systems)

Preference-based reinforcement learning: evolutionary direct policy search using a preference-based racing algorithm. - Busa-Fekete, Robert; Szörenyi, B.; Weng, P.; Cheng, W.; Hüllermeier, Eyke (Machine Learning)

Open challenges for data stream mining research - Krempl, G.; Zliobaite, I.; Brzezinski, D.; Hüllermeier, Eyke; Last, M.; Lemaire, V.; Noack, T.; Shaker, A.; Sievi, S.; Spiliopoulou, M.; Stefanowski, J. (SIGKDD Explorations)

Correlation-based embedding of pairwise score data - Strickert, M.; Bunte, K.; Schleif, F.M.; Hüllermeier, Eyke (Neurocomputing)

Survival analysis on data streams: Analyzing temporal events in dynamically changing environments - Shaker, Ammar; Hüllermeier, Eyke (International Journal of Applied Mathematics and Computer Science)

Reliable classification: Learning classifiers that distinguish aleatoric and epistemic uncertainty - Senge, Robin; Bösner, S.; Dembczynski, K.; Haasenritter, J.; Hirsch, O.; Donner-Banzhoff, N.; Hüllermeier, Eyke (Information Sciences)

The comprehensive diagnostic study is suggested as a design to model the diagnostic process - Donner-Banzhoff, N.; Haasenritter, J.; Hüllermeier, Eyke; Viniol, A.; Bösner, S.; Becker, A. (Journal of Clinical Epidemiology)

Fast Collisionless Pattern Formation by Anonymous, Position-Aware Robots - Lukovszki, Tamás; Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

Continuous Aggregation in Dynamic Ad-Hoc Networks - Abshoff, Sebastian; Meyer auf der Heide, Friedhelm (Structural Information and Communication Complexity)

Common Fate Graph Patterns in Monte Carlo Tree Search for Computer Go - Graf, Tobias; Platzner, Marco (2014 IEEE Conference on Computational Intelligence and Games)

PAC Rank Elicitation through Adaptive Sampling of Stochastic Pairwise Preferences - Busa-Fekete, Robert; Szörényi, B.; Hüllermeier, Eyke (Proceedings AAAI 2014, Quebec, Canada)

A Survey of Preference-Based Online Learning with Bandit Algorithms - Busa-Fekete, Robert; Hüllermeier, Eyke (Proceedings Int. Conf. on Algorithmic Learning Theory (ALT), Bled, Slovenia)

Mining Rank Data - Henzgen, Sascha; Hüllermeier, Eyke (Proceedings Discovery Science, Bled,Slovenia)

The Choquet kernel for monotone data - Fallah Tehrani, A.; Strickert, M.; Hüllermeier, Eyke (Proceedings ESANN , Bruges, Belgium)

Learning Solution Similarity in Preference-Based CBR - Abdel-Aziz, A.; Strickert, M.; Hüllermeier, Eyke (Proceedings Int. Conf. Case-Based Reasoning (ICCBR), Cork, Ireland)

Dyad Ranking Using A Bilinear Plackett-Luce Model - Schäfer, Dirk; Hüllermeier, Eyke (Proceedings Lernen-Wissensentdeckung-Adaptivität (LWA), Aachen, Germany)

Machine Learning and Knowledge Discovery in Databases-European Conf. ECML/PKDD, Nancy, France - Calders, T.; Esposito, F.; Hüllermeier, Eyke; Meo, R. (Proceedings, Parts I-III. Lecture Notes in Computer Science)

Preference Learning (Dagstuhl Seminar 14101) Dagstuhl Reports - Fürnkranz, J.; Hüllermeier, Eyke; Rudin, Cynthia; Slowinski, Roman; Sanner, Scott

Survival analysis on data streams: Analyzing temporal events in dynamically changing environments - Shaker, Ammar; Hüllermeier, Eyke (Applied Mathematics and Computer Science)

Ausgewählte Beiträge des GMA-Fachausschusses 5.14 - Hoffmann, F.; Hüllermeier, Eyke; Kroll, A. (Computational Intelligence Automatisierungstechnik)

Guest editors`introduction:special issue of the ECML/PKDD 2014 journal track - Calders, T.; Esposito, F.; Hüllermeier, Eyke; Meo, R. (Data Min. Knowledge Discovery)

Visualization of evolving fuzzy rule-based systems - Henzgen, Sascha; Strickert, M.; Hüllermeier, Eyke (Evolving Systems)

Learning from imprecise and fuzzy observations: Data disambiguation through generalized loss minimization - Hüllermeier, Eyke (Int. J. Approx. Reasoning)

Rejoinder on "Learning from imprecise and fuzzy observations: Data disambiguation through generalized loss minimization - Hüllermeier, Eyke (Int. J. Approx. Reasoning)

Correlation-based embedding of pairwise score data - Strickert, M.; Bunte, K.; Schleif, F.- M.; Hüllermeier, Eyke (Neurocomputing)

Reliable classification: Learning classifiers that distinguish aleatoric and epistemic uncertainty - Senge, Robin; Bösner, S.; Dembczynski, K.; Haasenritter, J.; Hirsch, O.; Donner-Banzhoff, N.; Hüllermeier, Eyke (Information Sciences)

Protein Sub-Cellular Localization Prediction for Special compartments via Optimized Time Series Distances - Mernberger, M.; Moog, M.; Stork, S.; Zauner, S.; Maier, U.G.; Hüllermeier, Eyke (J. Bioinformatics and Computational Biology)

Guest editors`introduction:special issue of the ECML/PKDD 2014 journal track - Calders, T.; Esposito, F.; Hüllermeier, Eyke; Meo, R. (Machine Learning)

Preference-Based Reinforcement Learning: evolutionary direct policy search using a preference-based racing algorithm - Busa-Fekete, Robert; Szörényi, B.; Weng, P.; Cheng, W.; Hüllermeier, Eyke (Machine Learning)

Dependent binary relevance models for multi-label classification - Montanés, E.; Senge, Robin; Barranquero, J.; Quevedo, J.R.; Del Coz, J.J.; Hüllermeier, Eyke (Pattern Recognition)

Open challenges for data stream mining research - Krempl, G.; Zliobaite, I.; Brzezinski, D.; Hüllermeier, Eyke; Last, M.; Lemaire, V.; Noack, T.; Shaker, Ammar; Sievi, S.; Spiliopoulou, M.; Stefanowski, J. (SIGKDD Explorations)

Extended Graph-Based Models for Enhanced Similarity Search in Cavbase - Krotzky, T.; Fober, T.; Hüllermeier, Eyke; Klebe, G. (IEEE/ACM Trans. Comput. Biology Bioinform.)

Identification of Functionally Releated Enzymes by Learning to Rank Methods - Stock, M.; Fober, T.; Hüllermeier, Eyke; Glinca, S,; Klebe, G.; Pahikkala, T.; Airola, A.; De Baets, B.; Wageman, W. (IEEE/ACM Trans. Comput. Biology Bioinform.)

Power model design for ICT systems – A generic approach - Beister, Frederic; Dräxler, Martin; Aelken, Jörg; Karl, Holger (Computer Communications)

Hardness of approximation for quantum problems - Gharibian, Sevag; Kempe, Julia (Quantum Information & Computation)
The polynomial hierarchy plays a central role in classical complexity theory. Here, we define a quantum generalization of the polynomial hierarchy, and initiate its study. We show that not only are there natural complete problems for the second level of this quantum hierarchy, but that these problems are in fact hard to approximate. Using the same techniques, we also obtain hardness of approximation for the class QCMA. Our approach is based on the use of dispersers, and is inspired by the classical results of Umans regarding hardness of approximation for the second level of the classical polynomial hierarchy [Umans, FOCS 1999]. The problems for which we prove hardness of approximation for include, among others, a quantum version of the Succinct Set Cover problem, and a variant of the local Hamiltonian problem with hybrid classical-quantum ground states.
Keywords: Hardness of approximation; polynomial time hierarchy; succinct set cover; quantum complexity

Gate-efficient discrete simulations of continuous-time quantum query algorithms - W. Berry, Dominic; Cleve, Richard; Gharibian, Sevag (Quantum Information & Computation)
We show how to efficiently simulate continuous-time quantum query algorithms that run in time T in a manner that preserves the query complexity (within a polylogarithmic factor) while also incurring a small overhead cost in the total number of gates between queries. By small overhead, we mean T within a factor that is polylogarithmic in terms of T and a cost measure that reflects the cost of computing the driving Hamiltonian. This permits any continuous-time quantum algorithm based on an efficiently computable driving Hamiltonian to be converted into a gate-efficient algorithm with similar running time.

Verschiebungen an der Grenze zwischen Hardware und Software - Platzner, Marco; Plessl, Christian (Logiken strukturbildender Prozesse: Automatismen)
Im Bereich der Computersysteme ist die Festlegung der Grenze zwischen Hardware und Software eine zentrale Problemstellung. Diese Grenze hat in den letzten Jahrzehnten nicht nur die Entwicklung von Computersystemen bestimmt, sondern auch die Strukturierung der Ausbildung in den Computerwissenschaften beeinﬂusst und sogar zur Entstehung von neuen Forschungsrichtungen geführt. In diesem Beitrag beschäftigen wir uns mit Verschiebungen an der Grenze zwischen Hardware und Software und diskutieren insgesamt drei qualitativ unterschiedliche Formen solcher Verschiebungen. Wir beginnen mit der Entwicklung von Computersystemen im letzten Jahrhundert und der Entstehung dieser Grenze, die Hardware und Software erst als eigenständige Produkte diﬀerenziert. Dann widmen wir uns der Frage, welche Funktionen in einem Computersystem besser in Hardware und welche besser in Software realisiert werden sollten, eine Fragestellung die zu Beginn der 90er-Jahre zur Bildung einer eigenen Forschungsrichtung, dem sogenannten Hardware/Software Co-design, geführt hat. Im Hardware/Software Co-design ﬁndet eine Verschiebung von Funktionen an der Grenze zwischen Hardware und Software während der Entwicklung eines Produktes statt, um Produkteigenschaften zu optimieren. Im fertig entwickelten und eingesetzten Produkt hingegen können wir dann eine feste Grenze zwischen Hardware und Software beobachten. Im dritten Teil dieses Beitrags stellen wir mit selbst-adaptiven Systemen eine hochaktuelle Forschungsrichtung vor. In unserem Kontext bedeutet Selbstadaption, dass ein System Verschiebungen von Funktionen an der Grenze zwischen Hardware und Software autonom während der Betriebszeit vornimmt. Solche Systeme beruhen auf rekonﬁgurierbarer Hardware, einer relativ neuen Technologie mit der die Hardware eines Computers während der Laufzeit verändert werden kann. Diese Technologie führt zu einer durchlässigen Grenze zwischen Hardware und Software bzw. löst sie die herkömmliche Vorstellung einer festen Hardware und einer ﬂexiblen Software damit auf.

Partitioning and Vectorizing Binary Applications for a Reconfigurable Vector Computer - Kenter, Tobias; Vaz, Gavin Francis; Plessl, Christian (Proceedings of the International Symposium on Reconfigurable Computing: Architectures, Tools, and Applications (ARC))
In order to leverage the use of reconfigurable architectures in general-purpose computing, quick and automated methods to find suitable accelerator designs are required. We tackle this challenge in both regards. In order to avoid long synthesis times, we target a vector copro- cessor, implemented on the FPGAs of a Convey HC-1. Previous studies showed that existing tools were not able to accelerate a real-world application with low effort. We present a toolflow to automatically identify suitable loops for vectorization, generate a corresponding hardware/software bipartition, and generate coprocessor code. Where applicable, we leverage outer-loop vectorization. We evaluate our tools with a set of characteristic loops, systematically analyzing different dependency and data layout properties.

Seven Recipes for Setting Your FPGA on Fire – A Cookbook on Heat Generators - Agne, Andreas; Hangmann, Hendrik; Happe, Markus; Platzner, Marco; Plessl, Christian (Microprocessors and Microsystems)
Due to the continuously shrinking device structures and increasing densities of FPGAs, thermal aspects have become the new focus for many research projects over the last years. Most researchers rely on temperature simulations to evaluate their novel thermal management techniques. However, these temperature simulations require a high computational effort if a detailed thermal model is used and their accuracies are often unclear. In contrast to simulations, the use of synthetic heat sources allows for experimental evaluation of temperature management methods. In this paper we investigate the creation of significant rises in temperature on modern FPGAs to enable future evaluation of thermal management techniques based on experiments. To that end, we have developed seven different heat-generating cores that use different subsets of FPGA resources. Our experimental results show that, according to external temperature probes connected to the FPGA’s heat sink, we can increase the temperature by an average of 81 !C. This corresponds to an average increase of 156.3 !C as measured by the built-in thermal diodes of our Virtex-5 FPGAs in less than 30 min by only utilizing about 21 percent of the slices.

Reconstructing AES Key Schedules from Decayed Memory with FPGAs - Riebler, Heinrich; Kenter, Tobias; Plessl, Christian; Sorge, Christoph (Proceedings of Field-Programmable Custom Computing Machines (FCCM))
In this paper, we study how AES key schedules can be reconstructed from decayed memory. This operation is a crucial and time consuming operation when trying to break encryption systems with cold-boot attacks. In software, the reconstruction of the AES master key can be performed using a recursive, branch-and-bound tree-search algorithm that exploits redundancies in the key schedule for constraining the search space. In this work, we investigate how this branch-and-bound algorithm can be accelerated with FPGAs. We translated the recursive search procedure to a state machine with an explicit stack for each recursion level and create optimized datapaths to accelerate in particular the processing of the most frequently accessed tree levels. We support two different decay models, of which especially the more realistic non-idealized asymmetric decay model causes very high runtimes in software. Our implementation on a Maxeler dataflow computing system outperforms a software implementation for this model by up to 27x, which makes cold-boot attacks against AES practical even for high error rates.
Keywords: coldboot

Self-awareness as a Model for Designing and Operating Heterogeneous Multicores - Agne, Andreas; Happe, Markus; Lösch, Achim; Plessl, Christian; Platzner, Marco (ACM Transactions on Reconfigurable Technology and Systems (TRETS))
Self-aware computing is a paradigm for structuring and simplifying the design and operation of computing systems that face unprecedented levels of system dynamics and thus require novel forms of adaptivity. The generality of the paradigm makes it applicable to many types of computing systems and, previously, researchers started to introduce concepts of self-awareness to multicore architectures. In our work we build on a recent reference architectural framework as a model for self-aware computing and instantiate it for an FPGA-based heterogeneous multicore running the ReconOS reconfigurable architecture and operating system. After presenting the model for self-aware computing and ReconOS, we demonstrate with a case study how a multicore application built on the principle of self-awareness, autonomously adapts to changes in the workload and system state. Our work shows that the reference architectural framework as a model for self-aware computing can be practically applied and allows us to structure and simplify the design process, which is essential for designing complex future computing systems.

ReconOS - An Operating System Approach for Reconfigurable Computing - Agne, Andreas; Happe, Markus; Keller, Ariane; Lübbers, Enno; Plattner, Bernhard; Platzner, Marco; Plessl, Christian (IEEE Micro)
The ReconOS operating system for reconfigurable computing offers a unified multi-threaded programming model and operating system services for threads executing in software and threads mapped to reconfigurable hardware. The operating system interface allows hardware threads to interact with software threads using well-known mechanisms such as semaphores, mutexes, condition variables, and message queues. By semantically integrating hardware accelerators into a standard operating system environment, ReconOS allows for rapid design space exploration, supports a structured application development process and improves the portability of applications

Runtime Resource Management in Heterogeneous System Architectures: The SAVE Approach - C. Durelli, Gianluca; Pogliani, Marcello; Miele, Antonio; Plessl, Christian; Riebler, Heinrich; Vaz, Gavin Francis; D. Santambrogio, Marco; Bolchini, Cristiana (Proc. Int. Symp. on Parallel and Distributed Processing with Applications (ISPA))

Deferring Accelerator Offloading Decisions to Application Runtime - Vaz, Gavin Francis; Riebler, Heinrich; Kenter, Tobias; Plessl, Christian (Proceedings of the International Conference on ReConFigurable Computing and FPGAs (ReConFig))
Reconfigurable architectures provide an opportunityto accelerate a wide range of applications, frequentlyby exploiting data-parallelism, where the same operations arehomogeneously executed on a (large) set of data. However, whenthe sequential code is executed on a host CPU and only dataparallelloops are executed on an FPGA coprocessor, a sufficientlylarge number of loop iterations (trip counts) is required, such thatthe control- and data-transfer overheads to the coprocessor canbe amortized. However, the trip count of large data-parallel loopsis frequently not known at compile time, but only at runtime justbefore entering a loop. Therefore, we propose to generate codeboth for the CPU and the coprocessor, and to defer the decisionwhere to execute the appropriate code to the runtime of theapplication when the trip count of the loop can be determinedjust at runtime. We demonstrate how an LLVM compiler basedtoolflow can automatically insert appropriate decision blocks intothe application code. Analyzing popular benchmark suites, weshow that this kind of runtime decisions is often applicable. Thepractical feasibility of our approach is demonstrated by a toolflowthat automatically identifies loops suitable for vectorization andgenerates code for the FPGA coprocessor of a Convey HC-1. Thetoolflow adds decisions based on a comparison of the runtimecomputedtrip counts to thresholds for specific loops and alsoincludes support to move just the required data to the coprocessor.We evaluate the integrated toolflow with characteristic loopsexecuted on different input data sizes.

Kernel-Centric Acceleration of High Accuracy Stereo-Matching - Kenter, Tobias; Schmitz, Henning; Plessl, Christian (Proceedings of the International Conference on ReConFigurable Computing and FPGAs (ReConFig))
Stereo-matching algorithms recently received a lot of attention from the FPGA acceleration community. Presented solutions range from simple, very resource efficient systems with modest matching quality for small embedded systems to sophisticated algorithms with several processing steps, implemented on big FPGAs. In order to achieve high throughput, most implementations strongly focus on pipelining and data reuse between different computation steps. This approach leads to high efficiency, but limits the supported computation patterns and due the high integration of the implementation, adaptions to the algorithm are difficult. In this work, we present a stereo-matching implementation, that starts by offloading individual kernels from the CPU to the FPGA. Between subsequent compute steps on the FPGA, data is stored off-chip in on-board memory of the FPGA accelerator card. This enables us to accelerate the AD-census algorithm with cross-based aggregation and scanline optimization for the first time without algorithmic changes and for up to full HD image dimensions. Analyzing throughput and bandwidth requirements, we outline some trade-offs that are involved with this approach, compared to tighter integration of more kernel loops into one design.

SAVE: Towards efficient resource management in heterogeneous system architectures - C. Durelli, Gianluca; Copolla, Marcello; Djafarian, Karim; Koranaros, George; Miele, Antonio; Paolino, Michele; Pell, Oliver; Plessl, Christian; D. Santambrogio, Marco; Bolchini, Cristiana (Proc. Int. Conf. on Reconfigurable Computing: Architectures, Tools and Applications (ARC))

Accelerating Finite Difference Time Domain Simulations with Reconfigurable Dataflow Computers - Giefers, Heiner; Plessl, Christian; Förstner, Jens (ACM SIGARCH Computer Architecture News)
Keywords: funding-maxup; tet_topic_hpc

Cell Mapping Techniques for Exploratory Landscape Analysis - Kerschke, Pascal; Preuss, Mike; Hernández, Carlos; Schütze, Oliver; Sun, Jian-Qiao; Grimme, Christian; Rudolph, Günter; Bischl, Bernd; Trautmann, Heike (EVOLVE — A Bridge between Probability, Set Oriented Numerics, and Evolutionary Computation V)
Exploratory Landscape Analysis is an effective and sophisticated approach to characterize the properties of continuous optimization problems. The overall aim is to exploit this knowledge to give recommendations of the individually best suited algorithm for unseen optimization problems. Recent research revealed a high potential of this methodology in this respect based on a set of well-defined, computable features which only requires a quite small sample of function evaluations. In this paper, new features based on the cell mapping concept are introduced and shown to improve the existing feature set in terms of predicting expert-designed high-level properties, such as the degree of multimodality or the global structure, for 2-dimensional single objective optimization problems.

A Multiobjective Evolutionary Algorithm Guided by Averaged Hausdorff Distance to Aspiration Sets - Rudolph, G; Schütze, O; Grimme, C; Trautmann, Heike (EVOLVE — A Bridge between Probability, Set Oriented Numerics, and Evolutionary Computation V)
The incorporation of expert knowledge into multiobjective optimization is an important issue which in this paper is reflected in terms of an aspiration set consisting of multiple reference points. The behaviour of the recently introduced evolutionary multiobjective algorithm AS-EMOA is analysed in detail and comparatively studied for bi-objective optimization problems w.r.t. R-NSGA2 and a respective variant. It will be shown that the averaged Hausdorff distance, integrated into AS-EMOA, is an efficient means to accurately approximate the desired aspiration set.

An Aspiration Set EMOA Based on Averaged Hausdorff Distances - Rudolph, Günter; Grimme, Christian; Schütze, Oliver; Trautmann, Heike (Proceedings of the Learning and Intelligent OptimizatioN Conference (LION 8))
We propose an evolutionary multiobjective algorithm that approximates multiple reference points (the aspiration set) in a single run using the concept of the averaged Hausdorff distance.

Stopping Criteria for Multimodal Optimization - Wessing, S; Preuss, M; Trautmann, Heike (Proceedings of the Parallel Problem Solving from Nature — PPSN XIII)
Multimodal optimization requires maintenance of a good search space coverage and approximation of several optima at the same time. We analyze two constitutive optimization algorithms and show that in many cases, a phase transition occurs at some point, so that either diversity collapses or optimization stagnates. But how to derive suitable stopping criteria for multimodal optimization? Experimental results indicate that an algorithm’s population contains sufficient information to estimate the point in time when several performance indicators reach their optimum. Thus, stopping criteria are formulated based on summary characteristics employing objective values and mutation strength.

Why eve and mallory (also) love webmasters - Fahl, Sascha; Acar, Yasemin; Perl, Henning; Smith, Matthew (Proceedings of the 9th ACM symposium on Information, computer and communications security)

HeroeS - A Framework for Heterogeneous Software-Intensive System Design with SystemC - Becker, Markus; Müller, Wolfgang; Stroop, Joachim; Kiffmeier, Ulrich (Design, Automation and Test in Europe DATE, University Booth, Dresden)

Probabilistic Analysis of Long-term Swarm Performance under Spatial Interferences - Khaluf, Yara; Birattari, Mauro; Rammig, Franz-Josef (Theory and Practice of Natural Computing, Nr. 8273, 2nd International Conference on the Theory and Practice of Natural Computing, TPNC 2013)

Early Phase Memory Leak Detection in Embedded Software Designs with Virtual Memory Management Model - Joy, M. tech. Mabel Mary; Müller, Wolfgang; Rammig, Franz-Josef (Proceedings of AVICPS 2013, Dez. 2013 IEEE Computer Society,)

AN ENERGY-EFFICIENT HEURISTIC FOR HARD REAL- TIME SYSTEM ON MULTI-CORE PROCESSORS - He, Da; Müller, Wolfgang (Proceedings of International Conference on Applied Computing (AC))

Aspect-Oriented Model-Driven Engineering for Embedded Systems Applied to Automation Systems - Wehrmeister, Marco A.; Pereira, Carlos E.; Rammig, Franz-Josef (IEEE Trans. on Industrial Informatics vol. 9 (no. 4))
Automation and control systems include many “intelligent” automation devices, which are usually implemented as complex embedded systems. New methods and tools are demanded to cope with the increasing design complexity, while keeping the project on schedule. Proper handling of nonfunctional system requirements is a key factor during the design of industrial automation systems, since in some application domains they are as important as (sometimes, more important than) functional requirements. This paper presents a model-driven engineering approach, which combines Unified Modeling Language (UML) and aspect-oriented software development (AOSD) to design real-time and embedded automation systems. The proposed approach allows a smooth transition from the initial phases to implementation by using software tools, comprising the system specification and the automatic generation of source code. By combining UML with model-level aspects and a script-base code generation tool, it enables the use of AOSD during system design and implementation, even though the target platform does not natively support such concepts. Experimental results on using this approach to design real-world examples of automation systems are presented. The results indicate a positive impact on the design of automation systems. The encapsulation of nonfunctional requirements was improved, increasing the reuse of developed artifacts. Generated source code statistics indicate that the proposed approach can generated a fair amount of code per model element.

Task Allocation Strategy for Time-Constrained Tasks in Robots Swarms - Khaluf, Yara; Rammig, Franz-Josef (ECAL 2013, 12th European Conference on Artificial Life)

Simulationsgestützter Entwurf für Elektrofahrzeuge - Farshizadeh, Emad; Briese, Herrmann; Steinmann, David; Stockmann, Lars; Beringer, Steffen; Holler, Dominik; Klobedanz, Kay; Heinzemann, Christian; Peter, Klaus; Leuer, Michael (8. Dortmunder Autotag, Sep. 2013)
Das Thema Elektromobilität hat in der Fahrzeugindustrie in den letzten Jahren viel Aufmerksamkeit erhalten. Gerade im Bereich der Entwicklung von Steuergeräte-Software ist der Bedarf an frühzeitiger Absicherung hoch. Nur so können Produkteinführungszeiten minimiert und effektiv Entwicklungskosten eingespart werden. Komplexe Werkzeugketten und die verteilte Entwicklung erschweren den Prozess und verlängern die Entwicklungszeit. Das Förderprojekt „Simulationsgestützter Entwurf für Elektrofahrzeuge“, kurz „E-Mobil“, nimmt sich der Herausforderungen einer verteilten Entwicklung von Steuergeräte-Software an. Vier Projektpartner aus Industrie und Forschung untersuchen die Besonderheiten sowohl bzgl. des Entwurfsprozesses, als auch der beteiligten Entwurfswerkzeuge im Vergleich zur konventionellen Fahrzeugentwicklung. Im Fokus stehen die Modellierung und die simulationsgestützte Absicherung in frühen Entwurfsstadien. Die Modellierung umfasst Regelungssoftware sowie die für die Simulation nötigen elektrischen und mechatronischen Komponenten. Die vorliegende Arbeit stellt die Kernthemen sowie aktuelle Ergebnisse aus dem Projekt vor.

Efficient Power Intent Validation Using Loosely-Timed Simulation Models - Mischkalla, Fabian; Müller, Wolfgang (23rd International Workshop on Power And Timing Modeling, Optimization and Simulation, Sep. 2013)

Learning Recommendation System for Automated Service Composition - Jungmann, Alexander; Kleinjohann, Bernd (Proceedings of the 10th IEEE International Conference on Services Computing (SCC))
The as a Service paradigm reflects the fundamental idea of providing basic coherent functionality in terms of components that can be utilized on demand. These so-called services may also be interconnected in order to provide more complex functionality. Automation of this service composition process is indeed a formidable challenge. In our work, we are addressing this challenge by decomposing service composition into sequential decision making steps. Each step is supported by a recommendation mechanism. If composition requests recur over time and if evaluations of composition results are fed back, a proper recommendation strategy can evolve over time through learning from experience. In this paper, we describe our general idea of modeling this service composition and recommendation process as Markov Decision Process and of solving it by means of Reinforcement Learning. A case study serves as proof of concept.

Proteus Hypervisor: Full Virtualization and Paravirtualization for Multi-Core Embedded Systems - Gilles, Katharina; Grösbrink, Stefan; Baldin, Daniel; Kerstan, Timo (International Embedded Systems Symposium, 17. - 19. Jun. 2013)

On the Homogeneous Multiprocessor Virtual Machine Partitioning Problem - Grösbrink, Stefan (International Embedded Systems Symposium, 17. - 19. Jun. 2013)

Organic Real-time Programming – Vision and Approaches towards Self-Evolving and Adaptive Real-time Software - Rammig, Franz-Josef; Khaluf, Lial; Montealegre, Norma; Stahl, Katharina; Zhao, Yuhong (Proc. 9th Workshop on Software Technologies for Future Embedded and Ubiquitous Systems (SEUS) 2013)

HeroeS: Virtual Platform Driven Integration of Heterogeneous Software Components for Multi-Core Real-Time Architectures - Becker, Markus; Kiffmeier, Ulrich; Müller, Wolfgang (16th IEEE Computer Society Symposium on Object/Component/Service-oriented Real-time Distributed Computing)

A Framework for Enhancing Dependability in Self-x Systems by Artificial Immune Systems - Rammig, Franz-Josef; Stahl, Katharina; Vaz, Gavin Francis (Proc. 4th IEEE Workshop on Self-Organizing Real-Time Systems (SORT) 2013)

Multilevel Planning for Self-Optimizing Mechatronic Systems - Rasche, Christoph; Ziegert, Steffen (Proceedings of The Fifth International Conference on Adaptive and Self-Adaptive Systems and Applications)

AIS-based Anomaly Detection for Self-X Systems - Stahl, Katharina (Proceedings of the First Organic Computing Doctoral Dissertation Colloquium (OC-DDC'13))

Safe Self-Evolving Embedded Software via System Virtualization - Grösbrink, Stefan; Rammig, Franz-Josef (3rd SBC Workshop on Autonomic Distributed Systems - WoSiDA 2013)

Fair Bandwidth Sharing among Virtual Machines in a Multi-criticality Scope - Grösbrink, Stefan; Almeida, Luis; de Sousa, Mario; Petters, Stefan M. (5th Workshop on Adaptive and Reconfigurable Embedded Systems (CPSWeek 2013))

Accelerating Online Model Checking - Qanadilo, Mona; Samara, Sufyan; Zhao, Yuhong (6'th Latin-American Symposium on Dependable Computing (LADC 2013))

Bildangereicherte Kartenerstellung zur Unterstützung bei Rettungseinsätzen - Stern, Claudius; Rasche, Christoph; Kleinjohann, Lisa; Kleinjohann, Bernd (11. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)